Tessituras, tramas e territorialidades das catadoras de mangaba na Barra dos Coqueiros-SE - Jesus, Patricia Santos de (2017)
The mangaba collectors for a long time had their extractive practices kept anonymous. In the course of the years beyond the recognition as a group differentiated by this traditional community, territorial modifications in the native areas of mangabeiras were identified. Therefore, the main objective of the research was to analyze the new territorialities constituted by the mangaba collectors from the insertion of PRODETUR in the municipality of Barra dos Coqueiros - SE. In this sense, the concern of the study turned around the recent territorial and environmental dynamics, as well as the interferences of tourist territorial policies in the municipality in the territory used by these extractive women of the mangaba. The research techniques used were bibliographical and documentary, field study, direct observation, photographic records, application of structured interview, performance of Rapid Participatory Diagnosis (DRP) and use of Social Cartography instruments. According to the diagnosis it was verified that the self-recognition and the identity relation that the mangaba collectors maintain with endemic species and with the "ground" of the Barra-Coqueirense municipality reinforce important aspects for the construction of defense of their ways of life. Another important result of the research indicates that in the municipality of Barra dos Coqueiros the process of territorialization of the remaining areas of mangabeiras was constituted by the pickers of mangaba. The deterritorialization of these areas had significant contributions in the face of government policy incentives for tourism development in the municipality and in road improvements that resulted in profound transformations in the access ways of the natural resources by the mangaba extractivists. Thus, reterritorialization appears as a threat to the permanence of this traditional community and its forms of knowledge and practices arising from the intimate relations with the ecosystems present in the locality.